Untying the Kibaran knot: a reassessment of Mesoproterozoic correlations in southern Africa based on SHRIMP U-Pb data from the Irumide belt - De Waele, Bert; Wingate, Michael; Fitzsimons, Ian; Mapani, B. (Geological Society of America, 2003)
The Irumide belt is part of a network of late Mesoproterozoic Kibaran-age orogens in south-central Africa. Sensitive high-resolution ion microprobe (SHRIMP) U-Pb zircon ages for gneisses, migmatites, and granitoids indicate that peak Irumide metamorphism was ca. 1020 Ma and that this was associated with widespread granitic magmatism at 1050–950 Ma. Pre-Irumide protoliths are dominated by 1650–1519 Ma granitic gneisses. These data provide the first robust constraint on the timing of Irumide tectonism and show that previous estimates of ca. 1350 and 1100 Ma are incorrect, thereby negating previously proposed correlations of the Irumide belt with nearby Kibaran-aged tectonism. The correlation between the Irumide belt and Choma-Kalomo block of southern Zambia has had a major influence on models for the tectonic assembly of southern Africa because it required that the intervening Neoproterozoic Zambezi belt was intracratonic and associated with minimal horizontal displacements. Our data indicate that both terranes have distinct histories, consistent with lithologic and metamorphic evidence of Neoproterozoic ocean closure along the Zambezi belt. This implies that the Kalahari and Congo cratons assembled during the Neoproterozoic and not during Kibaran-age tectonism, as previously believed. This new outlook on regional African tectonics supports a configuration of the Rodinia supercontinent that places the Congo craton well away from the Kalahari craton ca. 1000 Ma.